2017
DOI: 10.1002/fsn3.471
|View full text |Cite
|
Sign up to set email alerts
|

Allergens labeling on French processed foods – an Oqali study

Abstract: The French Observatory of Food Quality (Oqali) aims at collecting all nutritional data provided on labels of processed foods (nutritional information and composition), at branded products level, in order to follow nutritional labeling changes over time. This study carries out an overview of allergens labeling frequencies by distinguishing allergens used in recipes from those listed on precautionary statements, for the fourteen allergen categories for which labeling is mandatory according to European legislatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 9 publications
3
22
0
1
Order By: Relevance
“…No data about presence or absence of additives has been found in the literature for comparison purposes. In relation to allergenic compounds, labeling data have been reported in different food sectors, one of them being ‘delicatessen meat’, but no information on processed meat products is shown (26).…”
Section: Resultsmentioning
confidence: 99%
“…No data about presence or absence of additives has been found in the literature for comparison purposes. In relation to allergenic compounds, labeling data have been reported in different food sectors, one of them being ‘delicatessen meat’, but no information on processed meat products is shown (26).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is known that in the case of soy, for example, many ultraprocessed foods make use of the emulsifying additive lecithin in its formulation, which further increases the restriction of food consumption for allergic people, due to the use of a derivative from the soybean and not specifically of the soybean grain itself (Soon, 2018). Another study carried out in France with 17.309 foods showed that soy was present in 20% of food ingredient lists, however, only 12% of foods warned about this allergenic component (Battisti et al, 2017).This demonstrates the lack of product options for this group of people with restrictions on certain components or ingredients. Other studies also demonstrates the high frequency of these same allergens.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that PAL is widely used in Latin America (33.2% of food products) and that even the proportion of naturally allergen-free products with PAL is considerable (23.6%). Others have reported similar percentages of PAL (28.6%–39.9%) [ 14 , 15 , 37 ] or even higher (65%) [ 38 ]. The PAL statement “may contain traces of…” was the most commonly utilized statement, which agrees with other studies [ 15 , 38 ] but 32 other types of PAL were also identified in the present study.…”
Section: Discussionmentioning
confidence: 83%
“…The sample size consisted of all the packaged food products available on the shelves at the time of the survey. For products with multiple package sizes, only one size was included in the analysis to avoid bias [ 14 ]. Duplicate products found across the supermarkets in each country were recorded only once.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation